1/25 translocations in Blonde d'Aquitaine cattle in New Zealand - Pearce, P. D.; Ansari, H. A.; Maher, D. W.; Amarante, M. R V [UNESP]; Monro, T. L.; Hendrikse, W. L. (Taylor & Francis, 1997)
A Robertsonian centric fusion between chromosomes 1 and 25 in Blonde d'Aquitaine cattle in New Zealand is reported. This fused chromosome is the same as the widely reported 1/29 translocation chromosome with the difference in the numbering arising from inconsistencies in the G- and R-banded cattle karyotypes of the International System for Cytogenetic Nomenclature of Domestic Animals, 1989.